2011
DOI: 10.1128/jvi.00702-11
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues 253 and 591 of the PB2 Protein of Avian Influenza Virus A H9N2 Contribute to Mammalian Pathogenesis

Abstract: We investigated the tropism, host responses, and virulence of two variants of A/Quail/Hong Kong/G1/1997 (H9N2) (H9N2/G1) with D253N and Q591K in the PB2 protein in primary human macrophages and bronchial epithelium in vitro and in mice in vivo . Virus with PB2 D253N and Q591K had greater polymerase activity in minireplicon assays, induced more tumor necrosis factor alpha (TNF-α) in human macrophages, replicated better in differentiated normal human bronchial epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 25 publications
5
63
0
Order By: Relevance
“…To determine why these 37 H9N2 isolates showed different replication capability in mice, we focused on analyzing the differences in PB2 and HA of theses isolates because these two proteins of AIVs have been demonstrated to play crucial roles in cross-species infection of mammals (23,27,29,30,42). For the PB2 protein, all these isolates had avian type residues 627E and 701D, which are critical for mammalian adaptation (Table 2).…”
Section: Ha-190v Is Responsible For Enhanced Replication Of H9n2 Aivsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine why these 37 H9N2 isolates showed different replication capability in mice, we focused on analyzing the differences in PB2 and HA of theses isolates because these two proteins of AIVs have been demonstrated to play crucial roles in cross-species infection of mammals (23,27,29,30,42). For the PB2 protein, all these isolates had avian type residues 627E and 701D, which are critical for mammalian adaptation (Table 2).…”
Section: Ha-190v Is Responsible For Enhanced Replication Of H9n2 Aivsmentioning
confidence: 99%
“…Two other substitutions (N313D and N496S) in the HA of an H9N2 AIV have been shown to enhance binding to both ␣2,3-linked sialic acid (SA␣2,3) and SA␣2,6 receptors (27). Some amino acid mutations such as A316S in HA and M147L, D253N, A588V, Q591K, E627K, and D701N in PB2 have been identified to play a critical role in enhancing replication of AIVs in mammals (23,(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…The PB2 D253N substitution is in the NP binding and cap binding domain (27). This mutation has been described in an H9N2 backbone to increase replication and pathogenicity in mice (28). The PB2 D253N substitution was not identified in the P1 sample but was seen in 100% of reads in the RCP5 sample.…”
Section: Resultsmentioning
confidence: 95%
“…1 and 2). Mutational analysis revealed two mutations in lineage A (PB2 D253N and NS1/NEP D2N) that are known to increase infectivity and pathogenicity in other viral backgrounds (28,29). While these changes could affect the phenotype, there is evidence that the differing M segments have a large effect, as well.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Clade 2.3.2.1c H5N1 viruses may have already adapted to poultry before their introduction into migratory birds. Amino acids Q591 (Mok et al, 2011), E627 (Subbarao et al, 1993;Hatta et al, 2001) and D701 (Zhou et al, 2013) in the PB2 protein of the H5N1 viruses suggest that they have not yet adapted to mammalian hosts. No drug-resistance-associated mutations (H274Y in NA; S31N in M2 (Hay et al, 1985;Pinto et al, 1992)) were observed among migratory H5N1 viruses, suggesting that these H5N1 isolates are still sensitive to NA and M2 inhibitors.…”
Section: Molecular Characteristicsmentioning
confidence: 99%